Jalan Baru Tasawuf: Kajian tentang Gagasan Abu Bakr al-Kalabazi - Abdul Kadir Riyadi (TSAQAFAH, 2015)
This paper is an attempt to analyse the development of the sufistic idea in its early period by referring to the thought of Abu Bakr al-Kalabazi. It treats tasawuf not merely as codes of practices and rituals, but as a system of knowledge and episteme. The paper tries to show that what al-Kalabazi and other sufis like him have done is to expose intellectually the meaning and message of the spiritual side of Islam in a way that makes it possible to become an objective and integrated paradigm. The thought of al-Kalabazi to be more precise and is looked-upon here not as an independent paradigm but as part of the larger system of tasawuf developed over time by the sufis. Treating al- Kalabazi as a successor of Abu Nasr al-Sarraj, the paper argues that the thought of these two sufis complements each other, and that what the former has attempted to do was to fill the gap that the latter has left. The paper in other words, is interested in, 1) how the notion of epistemic continuity is reflected in the thought of al-Kalabazi, and 2) how al-Kalabazi may be understood as forming a chain within the larger intellectual tradition of tasawuf; a chain that may be regarded as new and unique in it’s own context. In this way, one may understand -it is hoped- that the process of becoming in which tasawuf is undergoing as a system of knowledge is never-ending, and that in every single sufi a transfer of discursive meaning is indeed inevitable.